Memórias de estudantes egressos do Ginásio de Aplicação da Faculdade Católica de Filosofia de Sergipe (1960-1968) - Santos, Joelza de Oliveira (2019)
This study is a historical approach of the Application Gymnasium of the Sergipe Catholic Faculty of Philosophy and its main objective is to understand the perceptions of graduates of the Application Gymnasium about the educational and cultural practices experienced throughout their school careers, in the period between 1960 and 1968. The work is inserted in the field of study of the History of Education, from the perspective of Cultural History, seeking theoretical support in Chartier (1990), from the concepts of appropriation, representations and practices, aiming to understand what was remembered by discourse and socially constructed cultural practices, based on Bosi (1994) and Pollak (1992; 1989), regarding the concept of memory and identity; Julia (2001), regarding the conception of school culture as a category of analysis; and Bourdieu (2002; 2007) regarding the concepts of cultural capital and cultural reproduction in the field of symbolic struggles. The Thematic Oral History methodology was used, based on Alberti (2013; 2004), Meihy and Holanda (2013; 2015) and Meihy and Ribeiro (2011) establishing memory reports as the main research source. This study uses as source eight interviews of the audiovisual collection of the Research, Documentation and Memory Center of the College of Application (Cemdap), resulting from the execution of the project "Perceptions of reality": Memories of students graduating from the College of Application (1960-1995) ; and eight performed by the author of this research. Therefore, it is a memorialistic research about the school career and the culture assimilated by the students graduated from the Gymnasium of Application of the Catholic Faculty of Philosophy of Sergipe, an educational institution created to serve as a field of internship and pedagogical experimentation, linked to the Catholic Faculty of Philosophy of Sergipe, which remains in the memory of its former students to the present day.